Salmonella Enteritidis forms biofilm under low temperatures on different food industry surfaces - Webber,Bruna (2019)
ABSTRACT: We evaluated the influence of temperature on the ability of Salmonella Enteritidis (SE) to form biofilms on stainless steel, polyethylene, and polyurethane surfaces under different hygiene procedures. These materials were placed on SE culture and incubated at 42±1 ºC, 36±1 ºC, 25±1 ºC, 9±1 ºC, and 3±1 ºC for 4, 8, 12, and 24 h. Hot water at 45 ºC and 85 ºC, 0.5% peracetic acid solution, and 1% quaternary ammonia were used for hygienization. Biofilm formation occurred at all temperatures evaluated, highlighting at 3 ºC which has not been reported as an ideal temperature for the adhesion of SE to these materials. The SE adhered more often to polyethylene surfaces than to polyurethane and stainless steel surfaces (P<0.05). Peracetic acid and water at 85 ºC had similar hygienization efficiency (P<0.05) followed by quaternary ammonia whereas water at 45 ºC was not effective. SE adhered to these materials under low temperatures which to date have been deemed safe for food preservation.